Acrophobia / Nur Ayuni Farisha Nor Wadi, Nor Syazwani Abdul Aziz and Naja Helwa Mat Nor - Nor Wadi, Nur Ayuni Farisha; Abdul Aziz, Nor Syazwani; Mat Nor, Naja Helwa (2020)
The meaning of acrophobia means fears of height. As an example when you are high off the ground you start to feel paralyzed or terrified. This show one of the symptoms of acrophobia. Furthermore, acrophobia is also the disease that most students in UiTM Cawangan Kelantan, Kampus Machang does not know about it and they assume it as a joke. There are also some students have acrophobia but they did not know they have it. It is because they do not have knowledge about acrophobia. Acrophobia can be treated through certain treatments.